(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The aim of this research is to study the current situation of Pagellus erythrinus (Linnaeus,1758) stocks, in the marine waters of Lattakia. In this research, 504 individuals were collected and studied, with an average length of (16.64 ± 2.62) cm. The results showed that the growth pattern of individuals of this type is isometric (longitudinal growth is greater than weight growth), and that the studied fish have a good ability to transform the available food and benefit from it, and the maximum age that fish of this type can reach is 16 years. The study also showed that the stocks of this species were exposed to overexploitation, as the mortality rates (natural as a result of hunting) were high, and the exploitation rate was high and close to the maximum allowable limit (E=0.4). The length and age at the first capture were very close to the length and age at the first recruitment, which means that the individuals were caught after they entered the exploitation area, and in both cases, it was smaller than the length at sexual maturity. This is considered as another indicator of the vulnerability of this species to over-exploitation. Therefore, a number of scenarios were tested to improve the actual status of this stock. The best suggested scenario was natural mortality rate (M = 0.4/year), and that the age at the first hunting is (tc=3) years, which would sustainably conserve stock of this specie and prevents overexploitation. Key words: Pagellus erythrinus, Fish stock assessment, Syrian coast